Microstructure modification of porous carbon induced by low-dosage manganese nitrate for high-performance supercapacitor electrode. (10th March 2022) - Yao, Youheng; Huang, Guangxu; Liu, Yang; Li, Yuanyuan; Han, Gaoxu; Kang, Weiwei; Xing, Baolin; Liu, Quanrun; Jia, Jianbo; Zhang, Chuanxiang
Highlights: Microstructure modification of porous carbon induced by low-dosage Mn(NO3 )2. Increased specific surface area with a maximum increment of 873 m 2 g −1 . Remarkably increased sp 2 carbon content under critical dosage of Mn(NO3 )2. Impressive energy density of 31.9 W h kg −1 at 492.3 W kg −1 in Li2 SO4 electrolyte. Abstract: Herein, we report a comprehensive modification of porous carbon via simple carbonization with the aid of low dosage Mn(NO3 )2 . The resultant CMPCx exhibit significantly increased specific surface area compared to untreated porous carbon, with a maximum increment of 873 m 2 g −1 . Under a critical dosage of Mn(NO3 )2, i.e., a mass ratio of Mn(NO3 )2 solution to porous carbon of 0.2, the resultant CMPC2 has remarkably increased sp 2 carbon content and appropriate MnO loading. Notably, CMPC2 delivers a high specific capacitance of 370 F g −1 at 1.0 A g −1 and superior rate performance (207 F g −1 at 100 A g −1 ) in three-electrode system using 6 M KOH electrolyte, with dramatically enhanced pseudocapacitive behavior. As symmetric supercapacitor electrode, CMPC2 has large specific capacitance of 309 and 227 F g −1 at 0.25 and 20 A g −1 in 6 M KOH electrolyte, respectively. And a capacitance retention of 94.87% can be retained after 10, 000 cycles at 10 A g −1, demonstrating excellent cycle stability. Furthermore, CMPC2 based supercapacitor yields impressive energy densities of 31.9 and 8.3 W h kg −1 at the power densities of 492.3 W kg −1 and 9.6 kW kg −1 in 1 M Li2 SO4 electrolyte, respectively. Graphical abstract: Image, graphical abstract